Analysis of Beijing Douzhir Microbiota by High-Throughput Sequencing and Isolation of Acidogenic, Starch-Flocculating Strains - Xu, Yunhe; Yu, Yang; Tian, Yumin; Su, Yuhong; Li, Xiaona; Zhang, Zhen; Zhu, Hongyan; Han, Jie; Zhang, Huajiang; Liu, Liying; Zhang, Lili (Frontiers in Microbiology, 2018)
Beijing Douzhir is a traditional Chinese fermented drink produced by the natural fermentation of mung beans as the raw material. Ma tofu is an edible by-product of Douzhir processing. Douzhir microbiota, particularly bacteria involved in the natural fermentation process, has not been clearly established, resulting in limited industrial Douzhir production. Here, three uncooked Douzhir samples (D group) and three uncooked Ma tofu samples (M group) (two replicates per sample) were collected from three manufacturers in different locations in Beijing. The composition and diversity of the bacterial communities in each sample were analyzed by high-throughput sequencing. In total, 637 operational taxonomic units (OTUs) were revealed in the D group through database alignment, and 656 OTUs were found in the M group. The Chao, ACE, and Shannon indices were not significantly different in Douzhir samples from different manufacturers (p > 0.05). Representatives of six phyla were found in all 12 samples. Dominant bacteria were isolated and identified using mung bean juice as the growth medium. In both Douzhir and Ma tofu samples, dominant bacteria belonging to Firmicutes and Proteobacteria comprised > 94% of the total microbiota. The dominant bacteria included members of the Lactococcus, Acetobacter, Streptococcus, and Lactobacillus genera. Considering the dominant-microbiota information, we employed a plate-separation technique and isolated two strains of acid-producing bacteria from the Douzhir and Ma tofu samples with starch-flocculating activity: Acetobacter indonesiensis and Lactococcus lactis subsp. lactis. Such strains can serve as a foundation for the standardized industrial production of Douzhir.